Answer:
Five more than a number
Step-by-step explanation:
Given
f(x)= -3x - 5
g(x)= 4x - 2
Find
(f - g)(x)
substitute the f and g values in (f - g)
(f - g)(x)= -3x - 5 - (4x - 2)
change the signs in parentheses because there is a negative sign in front of the parentheses
(f - g)(x)= -3x - 5 - 4x + 2
combine like terms
(f - g)(x)= -7x - 3
ANSWER: (f - g)(x)= -7x - 3
Hope this helps! :)
Answer:
1.2 feet long
Step-by-step explanation:
(1/50) * 60 = 1.2
Answer:
69.12
Step-by-step explanation:
Answer:
d=-4 and a=10
Step-by-step explanation:
The sum of a arithmetic sequence is given by (n/2)*(2a+(n-1)d). Comparing coefficients with the given Sn, we have; a-d/2=12 and d/2=-2, d=-4 and a=10.